(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper explores the theme of female submission in Henik Ibsen’s “A Doll’s House”. Through a critical analysis of the protagonist, Nora Helmer, it argues that Nora’s journey challenges societal expectations of female submissiveness